2021
DOI: 10.1186/s12917-021-02999-3
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur, fresh cassava root and urea independently enhanced gas production, ruminal characteristics and in vitro degradability

Abstract: Background Total fresh cassava root (FCR) production was 275 million tonnes in 2018 which equals 61.1 % of the total production, and Thailand produced 10.7 % FCR of the total production. FCR is one of the main energy source for ruminant. The limitation of FCR utilization is due to the presence of hydrogen cyanide (HCN). The study aimed to evaluate the effect of sulfur, urea and FCR at various levels on in vitro gas production, ruminal fermentation and in vitro degradability. The study hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Furthermore, Prachumchai et al [6] demonstrated that the number of cyanide-using rumen bacteria was depressed by up to 90% when increasing the dose of HCN supplementation. In agreement with previous work by Sumadong et al [8], who reported that the gas production from the insoluble fraction (b) and gas production at 96 h after incubation significantly declined by 12.3% and 15.0%, respectively, when increasing fresh cassava root as a HCN source from 300 mg to 400 mg. Therefore, the present result indicated that the maximum dose of KCN which did not adversely affect the kinetics of gas was not more than 450 ppm.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, Prachumchai et al [6] demonstrated that the number of cyanide-using rumen bacteria was depressed by up to 90% when increasing the dose of HCN supplementation. In agreement with previous work by Sumadong et al [8], who reported that the gas production from the insoluble fraction (b) and gas production at 96 h after incubation significantly declined by 12.3% and 15.0%, respectively, when increasing fresh cassava root as a HCN source from 300 mg to 400 mg. Therefore, the present result indicated that the maximum dose of KCN which did not adversely affect the kinetics of gas was not more than 450 ppm.…”
Section: Discussionsupporting
confidence: 93%
“…It does, however, contain a high concentration of HCN (90-114 mg/kg), which, if consumed, may cause toxicity to the animal [6]. Rumen bacteria may swiftly detoxify a low level of HCN in ruminants via rhodanese and beta mercapto Fermentation 2021, 7, 207 2 of 10 pyruvate sulfur transferase [7,8]. Providing the available sulfur sources might supply microorganisms with a synthesis rhodanese enzyme to degrade HCN.…”
Section: Introductionmentioning
confidence: 99%
“…The energy efficiency improved with the increased production of propionate and decreased production of acetate [ 60 ]. Because most carbohydrate fermentation by rumen bacteria results in a higher propionate concentration, an increase in propionate concentration often causes a drop in the ratio of acetate to butyrate in the rumen [ 61 ]. In this study, supplementation of XP yeast culture with 10 g/kg of substrate decreased the molar acetate proportion and increased the molar butyrate and valerate proportion at 48 h and decreased the ratio of acetate to proportion, suggesting that supplementation of XP yeast culture changed the fermentation pattern in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to FCR‐1.5, FCR‐2 significantly increased total VFA and propionate concentration. This could be explained by the increase in fermentable carbohydrate amount from FCR‐2 for ruminal microbe fermentation into VFAs, mainly propionate (Seankamsorn et al, 2021; Sommai et al, 2021; Sumadong et al, 2021). This result was consistent with the in vitro study, that propionate concentration was increased as FCR supplementation increased (Sumadong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the increase in fermentable carbohydrate amount from FCR‐2 for ruminal microbe fermentation into VFAs, mainly propionate (Seankamsorn et al, 2021; Sommai et al, 2021; Sumadong et al, 2021). This result was consistent with the in vitro study, that propionate concentration was increased as FCR supplementation increased (Sumadong et al, 2021). Similarly, Cherdthong et al (2018) revealed that supplementation of FCR at 15 g/kg BW in diets of Thai native beef cattle increased propionate concentration by 16% compared with 10 g/kg BW of FCR supplementation.…”
Section: Discussionmentioning
confidence: 99%